2020
DOI: 10.3390/cancers12030694
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Molecular Phenotyping of Organoids from the Squamocolumnar Junction Region of the Uterine Cervix

Abstract: The metaplastic epithelium of the transformation zone (TZ) including the squamocolumnar junction (SCJ) of the uterine cervix is a prime target of human papilloma virus (HPV) infection and subsequent cancer development. Due to the lack of adequate in vitro models for SCJ, however, investigations into its physiological roles and vulnerability to carcinogenesis have been limited. By using Matrigel-based three-dimensional culture techniques, we propagated organoids derived from the normal SCJ region, along with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 38 publications
(57 reference statements)
0
21
0
Order By: Relevance
“…Recently, Maru et al (2020) succeeded in establishing cervical organoids from a limited number of patient-derived biopsies in a medium supplemented with RSPO1, Noggin, EGF, ROCKi and the Notch ligand Jagged-1. The organoid cells expressed validated SCJ markers more robustly than classic cell lines and displayed both differentiated endo-and ectocervical cell types.…”
Section: Cervixmentioning
confidence: 99%
“…Recently, Maru et al (2020) succeeded in establishing cervical organoids from a limited number of patient-derived biopsies in a medium supplemented with RSPO1, Noggin, EGF, ROCKi and the Notch ligand Jagged-1. The organoid cells expressed validated SCJ markers more robustly than classic cell lines and displayed both differentiated endo-and ectocervical cell types.…”
Section: Cervixmentioning
confidence: 99%
“…The endocervical organoids express KRT7, whilst the ectocervical ones are positive for basal markers KRT5 and TP63. Organoids have also been derived from the cervical SCJ and grown in a medium containing EGF, RSPO1, Noggin, Y-27632, and Jagged-1 [95]. MMP7 and AGR2 are expressed in these organoids, which are also KRT17 + .…”
Section: Cervixmentioning
confidence: 99%
“…Organoids can be established from pathological samples and provide powerful tools to study diseases ex vivo although the culture conditions often need optimizing [69,78,95,[102][103][104][105][106][107][108][109][110][111] ( Table 4). A common benign condition is endometriosis where ectopic foci of the endometrium containing both glands and stroma are found in the peritoneal cavity, ovary, and cervix.…”
Section: Endometriosis and Endometrial Hyperplasiamentioning
confidence: 99%
“…Recent comprehensive studies deriving PDOs from cervical cancer cells or normal cervical tissue have been described. Organoids have been developed from normal cervical cells from the SCJ region, and metastatic squamous cells from the transformation zone, providing models in which HPV-driven cervical carcinogenesis could be evaluated [75]. Furthermore, organoids established from human and mouse ecto-and endo-cervical cells revealed that the two epithelial cell types descend from distinct cervical lineage-specific stem cell populations which are regulated by divergent stromal Wnt signals.…”
Section: Organoids Recapitulate the Main Characteristics And Tissue Hierarchy Of Epithelial Tumours In Vitro And Are A Potential Tool Formentioning
confidence: 99%